Bridging Theory and Practice: The Role of Contextual Teaching and Learning in Improving Student Performance in Madrasah - Novita, Mona; Rahayu, Sri; Pajrini, Ani (At-Tarbiyat, 2024)
This research focuses on the application of the Contextual Teaching and Learning (CTL) model in improving the learning outcomes of Natural Sciences (IPA) on simple aircraft materials at MTs Pondok Pesantren Al Fattah, Bungo Regency. The CTL model was chosen to help students relate the concepts learned to real-world experiences, which can strengthen understanding and practical skills. This study uses the Classroom Action Research (PTK) method with the Kemmis and Taggart models, which is carried out in two cycles with four stages: planning, action, observation, and reflection. Data was collected through tests, observations, and interviews, and analyzed qualitatively and quantitatively. The results of the study showed significant improvements in the cognitive, affective, and psychomotor aspects of students; where the completeness of learning outcomes increased from 35.71% in the first cycle to 85.71% in the second cycle. The implications of this study show that the CTL model is effective in increasing student involvement and understanding of science materials, especially in the context of Islamic boarding schools. The application of poster media and real objects also strengthens learning outcomes. Thus, the CTL model is recommended as an effective approach to teaching science materials that require practical understanding in a pesantren-based educational environment.